The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0103-97332007000500021
|View full text |Cite
|
Sign up to set email alerts
|

The chromo-weibel instability

Abstract: I discuss the physics of non-Abelian plasmas which are locally anisotropic in momentum space. Such momentum-space anisotropies are generated by the rapid longitudinal expansion of the matter created in the first 1 fm/c of an ultrarelativistic heavy ion collision. In contrast to locally isotropic plasmas anisotropic plasmas have a spectrum of soft unstable modes which are characterized by exponential growth of transverse chromomagnetic/-electric fields at short times. This instability is the QCD analogue of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Weibel instabilities are also excited in relativistic plasmas (Yoon and Davidson, 1987) and for relativistic shocks (Milosavljević et al, 2006). This type of instability is even derived from electroweak (Silva et al, 2000) and quark-gluonen plasmas (Arnold and Moore, 2006;Strickland, 2007) and is considered as an alternative source for quasi-stationary magnetic fields besides dynamos (Treumann and Baumjohann, 2012). Furthermore, in gyrotropic or unmagnetized plasmas the existence of a pure growing mode has also been shown based on general linear fluctuation theory and fluctuation-dissipation theorems .…”
Section: Instabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Weibel instabilities are also excited in relativistic plasmas (Yoon and Davidson, 1987) and for relativistic shocks (Milosavljević et al, 2006). This type of instability is even derived from electroweak (Silva et al, 2000) and quark-gluonen plasmas (Arnold and Moore, 2006;Strickland, 2007) and is considered as an alternative source for quasi-stationary magnetic fields besides dynamos (Treumann and Baumjohann, 2012). Furthermore, in gyrotropic or unmagnetized plasmas the existence of a pure growing mode has also been shown based on general linear fluctuation theory and fluctuation-dissipation theorems .…”
Section: Instabilitiesmentioning
confidence: 99%
“…5 (left) and the solar wind velocity as group velocity yielding L char = u 0SW /γ c ≈ 1000-1700 km ≈ L Amp . Hence, the modified ion-Weibel instability is a convective instability (Sturrock, 1958) propagated by the solar wind.…”
Section: Instabilitiesmentioning
confidence: 99%
“…In the static limit, for small θ n some of the scales appearing in the dispersion relations are negative implying that the whole system is unstable with respect to magnetic instability [17,18]. It has been demonstrated that in case of k n(θ n = 0), the growth rate of the filamentation instabilities is the largest [10,11,15].…”
Section: B Unstable Modesmentioning
confidence: 99%
“…Strikland presented arguments that during the Glasma phase, the initially approximately boost invariant distribution of particles is unstable with respect to formation of rapidity dependent density fluctuations [20]. The seeds of these fluctuations arise in the quantum wavefunctions for the hadrons, and over time become amplified to a magnitude typical of the Glasma fields.…”
Section: Matter In the Earliest Stages Of Hadronic Collisiosmentioning
confidence: 99%